Pengaruh Leverage, Profitabilitas, Dan Likuiditas Terhadap Imbal Saham - Garry Ferdinand, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research to examine the effect of Profitability, Leverage, liquidity and size of the Company's Stock Return Manufacturing Company in Indonesia Stock Exchange 2015-2017 with variable control which is liquidity to avoid biased result. This research is use secondary data which is quantitative. Sampling method is using purposive sampling and get 64 data as result. This study uses associative method and multiple linear regression analysis techniques and includes the classic assumption test. The result of this research shows that leverage has a positive and not significant effect on the stock return, profitability has a positive and significant effect on the stock return, and the liquidity has a positive and not significant effect on the stock return